In Silico Identification of Candidate Genes for Fertility Restoration in Cytoplasmic Male Sterile Perennial Ryegrass (Lolium perenne L.). (March 2016) - Sykes, Timothy; Yates, Steven; Nagy, Istvan; Asp, Torben; Small, Ian; Studer, Bruno
Abstract : Perennial ryegrass ( Lolium perenne L.) is widely used for forage production in both permanent and temporary grassland systems. To increase yields in perennial ryegrass, recent breeding efforts have been focused on strategies to more efficiently exploit heterosis by hybrid breeding. Cytoplasmic male sterility (CMS) is a widely applied mechanism to control pollination for commercial hybrid seed production and although CMS systems have been identified in perennial ryegrass, they are yet to be fully characterized. Here, we present a bioinformatics pipeline for efficient identification of candidate restorer of fertility ( Rf ) genes for CMS. From a high-quality draft of the perennial ryegrass genome, 373 pentatricopeptide repeat (PPR) genes were identified and classified, further identifying 25 restorer of fertility-like PPR ( RFL ) genes through a combination of DNA sequence clustering and comparison to known Rf genes. This extensive gene family was targeted as the majority of Rf genes in higher plants are RFL genes. These RFL genes were further investigated by phylogenetic analyses, identifying three groups of perennial ryegrass RFL s. These three groups likely represent genomic regions of active RFL generation and identify the probable location of perennial ryegrass PPR-Rf genes. This pipeline allows for the identification of candidate PPR-Rf genes from genomic sequence data and can be used in any plant species. Functional markers for PPR-Rf genes will facilitate map-based cloning of Rf genes and enable the use of CMS as an efficient tool to control pollination for hybrid crop production.